Landscape approach to flooded areas - an issue or a challenge? - Blagojević, Ivana (Geodetski vestnik, 2013)
Floods, as a more and more present problem in Europe and in Serbia, require special treatment inspatial planning and regulation of river basins. Aimed at spatial improvement of the area and through theanalysis of contemporary condition, this paper tends to emphasise a recognisable model for soothing a devastating influence of floods both in the settlementof Jaša Tomić (north-eastern Serbia, Vojvodina) and in the areas that are facing similar natural problems. Furthermore, the paper is aimed at improving the area on the composition level as well for the purposes of making it more attractive and recognisable onthe tourist market. Methodology is based on the characterisation of the area (landscape reading,elaboration of check lists) and identification of alternative scenarios. The most acceptable scenario forthe researched area was chosen among the four possible ones using the AHP analysis. The scenario was furtherdeveloped in the phase of idea development. Based on the above mentioned, it can be concluded thatthe problem should have a multidisciplinary approach and that it should be observed from sociological,geographical, organisational as well as landscape architectural aspect so that the most acceptable solutionto this problem and the environment could be found both for the local population and for other users of thearea. The aim was to create the area of sustainable character whose principle of Fight against Floods will be replaced with the concept Living with Floods. The above mentioned was achieved with the suggested scenario.
Keywords: floods; living with floods; poplave; prostorsko urejanje; spatial planning of flooded areas; sustainable development; trajnostni razvoj